Psychology - Calvin, Allen D. (Allyn and Bacon, Inc., 1961)
"For many of you, this is your first encounter with psychology as a science. As you are undoubtedly aware, it is difficult to escape from the influence of psychology in our present day existence. When you applied for admission to the college you are now attending, in all likelihood you took an examination constructed by psychologists. When you look for employment, are called into the Army, try to adopt a child, have difficulty with your academic work, need counseling, or engage in thousands of other activities you will encounter the application of psychology. All of these applications depend upon the work of research psychologists just as engineers depend upon the work of the physicist and physicians depend upon the work of the biologist. Our primary purpose in this book is to acquaint you with some of the basic concepts which evolved from research findings in psychology, and which serve as the scientific underpinning for its numerous applications. With this in mind, we have divided the text into five major content sections each written by a specialist in the area and a sixth section dealing with professional aspects of psychology"--Introduction.